Coffee Export Dynamics And Competitiveness: Evidence From A Hybrid ARDL–RCA Framework (Jurnal Agribisnis Indonesia, 2026)
Although Indonesia is one of the world’s major coffee producers, maintaining competitive export performance remains challenging due to global price volatility, variations in production quality, and changing trade conditions. This study examines Indonesia’s coffee export performance using a hybrid market outcome framework that integrates the Revealed Comparative Advantage (RCA) index with an Autoregressive Distributed Lag (ARDL) approach. Annual time-series data from 2001 to 2023 are employed to analyze both short-run dynamics and long-run relationships among coffee exports, production volume, exchange rates, and export competitiveness. The empirical results indicate that Indonesia exhibits a moderate comparative advantage in coffee exports, although its RCA level remains lower than that of Brazil, Vietnam, and Colombia. The ARDL–ECM results confirm the existence of a long-run equilibrium relationship, where coffee production and export competitiveness significantly influence export performance, while exchange rate movements do not exert a significant long-run effect. In the short run, fluctuations in exchange rates and competitiveness contribute to export adjustments, reflecting price and market responsiveness. These findings suggest that Indonesia’s coffee export performance is shaped by the interaction between domestic production capacity and relative market competitiveness rather than by price factors alone. From a policy perspective, the results underscore the importance of improving product quality, enhancing market diversification, and aligning trade policies to strengthen export competitiveness. This study is limited by its single-country focus and the absence of explicit importer-side demand variables, indicating that future research may incorporate non-price factors and multi-country analyses to provide a broader understanding of global coffee trade dynamics.